Penguatan Kemandirian Ekonomi Masyarakat Eks Syi’ah Pasca Rekonsiliasi Konflik di Rusun Jemundo Sidoarjo - Taufiq, Amal; Rohman, Abid; Masrifah, Liya Hilyatul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The focus of this community service is to know how the ex. Syiah community in the Jemundo Sidoarjo Flats are fulfilling their daily economic needs, especially preparing for living generally in their home area of Sampang Madura. This service aims to provide participatory assistance to the community of ex-Shiah followers who have returned to Sunni teachings in the Jemundo Flats using a collaborative process between community organizations and university academic researchers to increase community capacity assets after being identified collectively, whether in the form of individual, group or institutional assets. This activity results in increased literacy skills in cultivating ornamental birds, skills in captivity, determining the location and size, supporting equipment for the cage, and maintaining its cleanliness. Meanwhile, the development of Madura petis products can be seen in the ability of attractive product packaging as well as selling skills and the inclusion of an expiration date.